Pertanggungjawaban Pidana Terhadap Tindak Pidana Aborsi Tanpa Izin - Khairil Fahmi Daulay; Janner Damanik (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The criminal offense of illegal abortion constitutes a crime against human life that violates the provisions of Indonesian criminal law as well as moral and ethical norms. This study aims to analyze the juridical classification of illegal abortion, the forms of criminal liability imposed on perpetrators, and the grounds for the exclusion of criminal liability as stipulated by law. The research employs a normative legal research method using both the statutory approach and the conceptual approach by examining primary and secondary legal materials. The findings indicate that illegal abortion is generally prohibited under both the former Indonesian Criminal Code (KUHP) and the new Criminal Code (Law No. 1 of 2023), and is further regulated mutatis mutandis under the Health Law (Law No. 17 of 2023). Criminal liability may be imposed on perpetrators—including women who intentionally terminate their pregnancies, medical professionals, and third parties who assist in the procedure—provided that they possess criminal responsibility, act with intent (dolus), and no grounds for justification or excuse apply. Exceptions to criminal liability are recognized only where abortion is performed on the basis of a medical emergency or in cases involving victims of rape or sexual violence resulting in pregnancy, provided that the procedure is carried out in accordance with accredited medical standards and the applicable legal requirements.